Community Engagement in Higher Education
XX, 334 p.
Keywords: There seems to be renewed interest in having universities and other higher education institutions engage with their communities at the local, national, and international levels. But what is community engagement? Even if this interest is genuine and widespread, there are many different concepts of community service, outreach, and engagement. The wide range of activity encompassed by community engagement suggests that a precise definition of the “community mission” is difficult and organizing and coordinating such activities is a complex task. This edited volume includes 18 chapters that explore conceptual understandings of community engagement and higher education reforms and initiatives intended to foster it. Contributors provide empirical research findings, including several case study examples that respond to the following higher educaiton community engagement issues. What is “the community” and what does it need and expect from higher education institutions? Is community engagement a mission of all types of higher education institutions or should it be the mission of specific institutions such as regional or metropolitan universities, technical universities, community colleges, or indigenous institutions while other institutions such as major research universities should concentrate on national and global research agendas and on educating internationally-competent researchers and professionals? How can a university be global and at the same time locally relevant? Is it, or should it be, left to the institutions to determine the scope and mode of their community engagement, or is a state mandate preferable and feasible? If community engagement or “community service” are mandatory, what are the consequences of not complying with the mandate? How effective are policy mandates and university engagement for regional and local economic development? What are the principal features and relationships of regionally-engaged universities? Is community engagementto be left to faculty members and students who are particularly socially engaged and locally embedded or is it, or should it be, made mandatory for both faculty and students? How can community engagement be (better) integrated with the (other) two traditional missions of the university—research and teaching? Cover image: The Towering Four-fold Mission of Higher Education, by Natalie Jacob.